Efficient synthesis of 2,4-disubstituted thiazoles using ionic liquid under ambient conditions: a practical approach towards the synthesis of Fanetizole - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2007)
A highly efficient and rapid synthesis of 2-amino-4-arylthiazoles and 2-methyl-4-arylthiazole from alpha-bromoketone and thiourea/thioamide is described using room temperature ionic liquid at ambient conditions. The method is simple, rapid and practical, generating thiazole derivatives in excellent isolated yields. This protocol is utilized for a commercially feasible synthesis of an anti-inflammatory agent, Fanetizole. (c) 2007 Published by Elsevier Ltd.
Keywords: alpha-bromo ketone; ionic liquids; thiazoles; thiourea/thioamide

Efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in an ionic liquid/water system under ambient conditions - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in ionic liquid/water solvent system is described. The paper describes synthesis of 2-amino-1,3-selenazoles by condensation of various phenacyl bromide with selenourea under ambient conditions in short reaction times. This protocol has notable advantages such as the absence of any added catalyst, simple operation and excellent yields of products and recyclability of the ionic liquid.
Keywords: 2-Amino-1; 3-selenazoles; ambient conditions; heterocycles; ionic liquid/water system; selenoureas; substituted phenacyl bromide

Efficient synthesis of quinoxalines in the ionic liquid 1-n-butylimidazolium tetrafluoroborate ([Hbim]BF4) at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Quinoxaline derivatives have been synthesized in excellent yields using an ionic liquid (IL) (viz., 1-n-butylimidazolium tetrafluoroborate) as a reaction medium as well as promoter from various 1,2-diketones and aryl-1,2-diamines. The process is general for the synthesis of quinoxaline derivatives from aromatic as well as aliphatic-1,2-diketones. The advantages of the present method are ambient reaction temperature, simplicity of operation, high yields of products, the recyclability of the IL, and ecofriendly nature of the reaction medium.
Keywords: 1; 2-diamines; 2-Diketones; Aryl-1; ionicliquid(IL); quinoxalines